Derajat Pemulihan dan Persentase Spermatozoa X dan Y Kambing Peranakan Etawah Setelah Separasi dengan Gradient Percoll (RECOVERY RATE AND PERCENTAGE OF SPERMATOZOA X AND Y OF ETAWAH CROSSBREED GOAT AFTER SEXING WITH GRADIENTT PERCOLL) - Rasad, Siti Darodjah; Setiawan, Rangga; Solihati, Nurcholidah; Widyastuti, Rini; Nugraha, Ilham (Jurnal Veteriner; Vol 20 No 1 (2019), 2019)
Aim of the research is to find out recovery rate and percentage spermatozoa X and Y after sexing with gradientt Percoll in Etawah Crossbreed Goat.  Extender was used TRIS Egg Yolk.  The semen sample from five male Etawah Crossbreed Goat were used in this research.  Gradientt percoll performed 10 fraction layer with centrifugation time 10 minute at 2500 rpm.  The data were analyzed descriptively. Result of the research shows that average recovery rate of spermatozoa X is 50.96±26.07 %  and  spermatozoa Y is 44.13±6.11 %.  Average percentage of  X sperm is 78.00±7.06 % and Y sperm is 76.10±5.95 % .